2006
DOI: 10.3748/wjg.v12.i43.7025
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus transmission and its risk factors within families of patients infected with hepatitis C virus in southern Iran: Khuzestan

Abstract: Intrafamilial transmission of HCV is not the significant transmission route and sexual transmission does not seem to play a role in the intrafamilial spread of HCV infection. Intrafamilial transmission of HCV is possible but occurs at a low rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 19 publications
4
20
0
1
Order By: Relevance
“…Intrafamilial transmission of HCV is considered as a nonsignificant route of transmission, and sexual transmission does not seem to play a role in the intrafamilial spread of HCV infection 18,19 . However, same studies have demonstrated significant anti-HCV prevalence rates in family members of patients with chronic HCV and/or in household contacts of anti-HCV-positive individuals 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Intrafamilial transmission of HCV is considered as a nonsignificant route of transmission, and sexual transmission does not seem to play a role in the intrafamilial spread of HCV infection 18,19 . However, same studies have demonstrated significant anti-HCV prevalence rates in family members of patients with chronic HCV and/or in household contacts of anti-HCV-positive individuals 20 .…”
Section: Discussionmentioning
confidence: 99%
“…6 On the other hand, according to some other published data, the prevalence of HCV infection in Iran is 0.59% to 0.8%. 7 Moreover, HCV infection among Iranian prisoners is high, despite low HCV seroprevalence in the general population. 8 According to some reports, up to 40% of Iranian prisoners who are intravenous drug users (IDUs or IVDAs) are positive for anti-HCV antibody (Ab).…”
Section: Hepatitis Cmentioning
confidence: 99%
“…This infection is a virulent health problem affecting more than 170 million people worldwide. The prevalence rate of HCV infection is from 0.2 up to 40% in different countries (2, 3) (about 0.2 to 2.2% in developed countries and nearly 7% in developing countries) (4). The prevalence of HCV infection is less than 0.5% (0.1% in women and 1.0% in men) in the general population of Iran (5) and this infection is common in hemophilia, thalasemia, hemodialysis patients and in intravenous drug users (IVDU) (6, 7).…”
Section: Introductionmentioning
confidence: 99%